Evaluation of Analytical Performances of Magnetic Force-Assisted Electrochemical Sandwich Immunoassay for the Quantification of Carcinoembryonic Antigen - Hwang, Boo Young; Kim, Eunsoo; Kim, Seung-ha; Hwang, Hyundoo (Frontiers in Bioengineering and Biotechnology, 2022)
Carcinoembryonic antigen (CEA) is a biomarker indicated in different cancers, targeted for quantitative analysis via immunoassay. Here we introduce a new technique called magnetic force-assisted electrochemical sandwich immunoassay (MESIA) for determination of CEA level in a drop of human serum using a fully automated point-of-care testing (POCT) device. The analytical performances of the assay are assessed based on precision, accuracy, limit of blank (LoB), limit of detection (LoD) and limit of quantitation (LoQ), linearity, Hook effect, interference, cross-reactivity, and method comparison following the guidelines of the Clinical Laboratory Standards Institute (CLSI). The LoD is 0.50 ng/mL. A linear relationship is shown in the range of 0.5-200 ng/mL. A high dose effect is not seen up to approximately 500,000 ng/mL. The recovery range is from 94.7% to 108.9%. The %CV of run-to-run and within-lab variations are less than 2.04% and 4.41% across the CEA concentrations, respectively, whereas reproducibility is 4.45-6.24%. Method comparison shows that the assay correlates well with the reference device (R²=0.9884). The assay demonstrates acceptable precision, accuracy, LoB, LoD and LoQ, hook effect, linearity, interference, cross-reactivity, and high correlation with its reference device. Thus, the system is suitable for the quantification of CEA in clinical practices with a POCT manner.